Expression of K1 Toxin Derivatives in Saccharomyces cerevisiae Mimics Treatment with Exogenous Toxin and Provides a Useful Tool for Elucidating K1 Mechanisms of Action and Immunity - Stefanie Gier; Manfred J. Schmitt; Frank Breinig (Toxins, 2017)
Killer toxin K1 is a heterodimeric protein toxin secreted by Saccharomyces cerevisiae strains infected with the M1 double-stranded RNA ‘killer’ virus. After binding to a primary receptor at the level of the cell wall, K1 interacts with its secondary plasma membrane receptor Kre1p, eventually leading to an ionophoric disruption of membrane function. Although it has been under investigation for decades, neither the particular mechanisms leading to toxicity nor those leading to immunity have been elucidated. In this study, we constructed derivatives of the K1α subunit and expressed them in sensitive yeast cells. We show that these derivatives are able to mimic the action of externally applied K1 toxin in terms of growth inhibition and pore formation within the membrane, leading to a suicidal phenotype that could be abolished by co-expression of the toxin precursor, confirming a mechanistic similarity of external and internal toxin action. The derivatives were successfully used to investigate a null mutant completely resistant to externally applied toxin. They provide a valuable tool for the identification of so far unknown gene products involved in K1 toxin action and/or immunity.